Viscosity effects on the dynamics of diols and diol-based deep eutectic solvents - Chatterjee, Srijan; Deshmukh, Samadhan H.; Chowdhury, Tubai; Bagchi, Sayan (Photochemistry and Photobiology, 2024)
Diols, characterized by the presence of two hydroxyl groups, form extended hydrogen-bonded networks. Increasing hydrocarbon chain length is known to elevate the viscosity of diols. Given the established influence of viscosity on solvent dynamics, it becomes imperative to comprehend the impact of viscosity on the fluctuation dynamics within diols and establish connections with hydrogen bond formation and breaking dynamics. In this study, we employ two-dimensional infrared spectroscopy to investigate the viscosity dependence of the structural evolution dynamics in three diols with varying chain lengths. Complementing our experimental approach, molecular dynamics simulations are conducted to extract hydrogen bond lifetimes. Our findings reveal a linear correlation between bulk viscosity, solvent fluctuation timescales, and hydrogen bond lifetimes. Notably, the selected diols exhibit the capability to form deep eutectic solvents upon mixing with choline chloride at specific molar ratios. In contrast to molecular solvents like diols, deep eutectic solvents are characterized by the formation of heterogeneous nanodomains, comprising various intercomponent hydrogen-bonded networks. Interestingly, our observations indicate that while the fluctuation dynamics decelerate with increasing bulk viscosity in diol-based deep eutectic solvents, the relationship between viscosity and dynamics is not linear, in contrast to the observed linearity in diols. This nuanced understanding contributes to the broader comprehension of the interplay between viscosity and dynamics in both molecular and deep eutectic solvents. We investigate the impact of viscosity on structural evolution dynamics in diols with varying chain lengths. Employing two-dimensional infrared spectroscopy and molecular dynamics simulations, we explore the relationship between bulk viscosity, solvent fluctuation timescales, and hydrogen bond lifetimes. We report a linear correlation in diols between viscosity, fluctuation timescales, and hydrogen bond lifetimes. Diols also form deep eutectic solvents, characterized by heterogeneous nanodomains. While fluctuation dynamics slow down with increasing bulk viscosity in diol-based deep eutectic solvents, the relationship between viscosity and dynamics is nonlinear, contrasting with diols' linearity. This understanding enhances comprehension of viscosity-dynamics interplay in molecular and deep eutectic solvents.image
Keywords: Dynamics; Hydrogen bond; solvent; spectroscopy; viscosity